2011
DOI: 10.1142/s1088424611003550
|View full text |Cite
|
Sign up to set email alerts
|

Development of the synthesis of the diamine complexes of covalent conjugates of platinum(II) with octacarboxy-substituted cobalt phthalocyanine

Abstract: Ethylenediamine-N,N′-diacetic acid complexes of the covalent conjugates of octacarboxy-substituted cobalt phthalocyanine with one, two and three platinum atoms (3a–c) were synthesized and characterized by elemental analysis, electronic absorption, infrared and mass spectra data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Spectra of compounds 2a-d (Figure 1) closely resemble the IR spectra of EDDA containing CCs of platinum(II) and octacarboxysubstituted PcCo II which have been reported previously [5] . It is known that the IR spectra of the compounds containing chelate rings with the metal atoms involved demonstrate two bands in the 1500-1560 cm -1 region [13] .…”
Section: Synthesissupporting
confidence: 79%
See 2 more Smart Citations
“…Spectra of compounds 2a-d (Figure 1) closely resemble the IR spectra of EDDA containing CCs of platinum(II) and octacarboxysubstituted PcCo II which have been reported previously [5] . It is known that the IR spectra of the compounds containing chelate rings with the metal atoms involved demonstrate two bands in the 1500-1560 cm -1 region [13] .…”
Section: Synthesissupporting
confidence: 79%
“…[4] Complexes with two and three ammine platinum fragments have been synthesized for the first time. New EDDA containing complexes of CCs of Pt II and octacarboxy-substituted PcZn 2a-d were synthesized using three-stage method analogous to [5] (Scheme 1). The number of platinum atoms in each case was controlled by the stoichiometry of starting materials and was confirmed by elemental analysis data.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[44] The solubility of the conjugate was attempted to be improved through using a modified amine ligand in place of the aqua-ligands but the compound was still insoluble and could not be biologically tested. [45] No emission data was recorded meaning it was difficult to determine if the radiative decay pathway had been quenched and how effective the compound would be as a photothermal agent.…”
Section: Conjugatedmentioning
confidence: 99%
“…Kalya and co-workers have shown that analogues with partial platinum ions coordination to octacarboxyphthalocyanines lead to formation of asymmetric platinum-containing derivatives 97 potentially useful in combinational cancer therapy ( Figure 6). 276 …”
Section: Peripheral Substituent Coordination Approachmentioning
confidence: 99%